Creative thinking ability and cognitive knowledge: Big Five personality - Jonni Sitorus; Nirwana Anas; Ermaliana Waruhu (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
This research aims at describing the ability and level of student’s creative thinking and student’s cognitive knowledge. It is qualitative research to search for data and information. Operationally, this research was conducted with some steps namely: (1) giving a set of big five personality test to 215 students to determine their personality type, (2) giving a set of creative thinking test of 215 students to measure the ability and level of their creative thinking, and (3) choosing one student randomly from each student’s personality type to be interviewed to search their cognitive knowledge. The results show that every student has a creative thinking ability, but the level of creative thinking varies. The category of student’s creative thinking ability based on Big Five Personalities is 'moderate or high'. The level of student’s creative thinking based on the big five personality is 'very creative, creative, quite creative or less creative'. The student’s cognitive knowledge based on the big five personality is drawing, designing, ascertaining, dividing, reasoning, analogy, imagining, utilizing, solving, understanding, determining, mentioning, and using trial and error.